2006
DOI: 10.1103/physrevb.74.041402
|View full text |Cite
|
Sign up to set email alerts
|

Lateral adsorption geometry and site-specific electronic structure of a large organic chemisorbate on a metal surface

Abstract: A combined study of scanning tunneling microscopy ͑STM͒ and density functional theory ͑DFT͒ reveals that 3,4,9,10-perylene-tetracarboxylic-dianhydride ͑PTCDA͒ adsorbs on Ag͑111͒ at bridge sites in two nonequivalent orientations, one nearly aligned with the ͓101͔ substrate axis and the other 18°misaligned. Site-specific spectroscopy reveals that molecules in the two configurations exhibit subtle differences in their electronic structure. DFT-based STM simulations trace these back to the influence of distinct lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
174
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(198 citation statements)
references
References 18 publications
23
174
1
Order By: Relevance
“…Our study is concluded with a very well-characterized HMOS: PTCDA on Ag(111) [59,60]. The presence of the functional group O=C−O−C=O on both sides of PTCDA enhances the bonding with the metallic surface.…”
Section: From Simple To Complex Interfacesmentioning
confidence: 91%
“…Our study is concluded with a very well-characterized HMOS: PTCDA on Ag(111) [59,60]. The presence of the functional group O=C−O−C=O on both sides of PTCDA enhances the bonding with the metallic surface.…”
Section: From Simple To Complex Interfacesmentioning
confidence: 91%
“…The level below ε F is the former LUMO that gets filled on adsorption and that is clearly observed in scanning tunneling spectroscopy. [26][27][28] The sharp level above ε F that is found in DFT appears in experiments as a broader feature in the gap between the former LUMO and the LUMO + 1, especially for molecules at the edges of monolayer islands. In our minimal model Hamiltonian we can only take one transport level into account.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of the chemical bonding of PTCDA to Ag(111) includes hybridization of the molecular orbitals with the substrate states, charge transfer between the substrate and the molecule, local bonds of the carboxylic oxygens to silver atoms below, and an extended bond of the molecular π system to the surface. 5,[26][27][28] Assuming that the two metastable positions can be well represented by a (not necessarily symmetric) double-well potential, the transfer of an adsorbate between the two minima may involve a variety of physical processes, such as (i) thermal activation, (ii) quantum tunneling, (iii) a transition through an electronic excited state with no conformational bi-stability, or (iv) vibrational heating. Process (i) is of minor interest in this work, since the experiments are performed at very low temperatures (5-6 K) and the barrier height is larger than 100 meV, which excludes the thermal activation.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations